2017
DOI: 10.6018/analesps.33.2.249381
|View full text |Cite
|
Sign up to set email alerts
|

Bullying/Cyberbullying en quinto y sexto curso de primaria: diferencias entre centros públicos y privados

Abstract: <p>The study aimed to analyse the prevalence of bullying/cyberbullying and to study the level of bullying/cyberbullying suffered, perpetrated and observed in public and private schools. Using a descriptive cross-sectional design, the test "Cyberbullying: Screening of peer harassment” was administered to a sample of 1,993 pupils from the Basque Country attending 5<sup>th</sup> and 6<sup>th</sup> grade of elementary school, 49% in public and 51% in private schools. The results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
1
17
0
10
Order By: Relevance
“…The dissonance of these results may be due to differences in ages of the samples since most of the prior studies used adolescent samples. Since bullying behavior has been shown to begin in primary school [ 53 , 54 , 55 ], it is likely that the high scores on aggressiveness develop with time of exposure and not during the initial contacts, which may lead to an overlapping of roles in subsequent grades and the development of a victimized bully role, whose aggressiveness indices have been found to be higher [ 38 , 68 ]. Similarly, it is important to consider the perspective of students with regard to aggressive behavior, given that for minors, some types of aggressiveness, such as verbal, are not considered to be cyberbullying behaviors, since they are used to facilitate communication and interaction with their peers, which would explain why all declarations of aggressiveness are not related to the cybervictim role [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissonance of these results may be due to differences in ages of the samples since most of the prior studies used adolescent samples. Since bullying behavior has been shown to begin in primary school [ 53 , 54 , 55 ], it is likely that the high scores on aggressiveness develop with time of exposure and not during the initial contacts, which may lead to an overlapping of roles in subsequent grades and the development of a victimized bully role, whose aggressiveness indices have been found to be higher [ 38 , 68 ]. Similarly, it is important to consider the perspective of students with regard to aggressive behavior, given that for minors, some types of aggressiveness, such as verbal, are not considered to be cyberbullying behaviors, since they are used to facilitate communication and interaction with their peers, which would explain why all declarations of aggressiveness are not related to the cybervictim role [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…As seen in the reviewed studies, cyberbullying causes major harm to its victims. Most of the studies use adolescent samples, despite the fact that the scientific literature has shown that cyberbullying also takes place during late childhood [ 53 , 54 , 55 ]. Therefore, the assessment of cybervictimization needs to also be carried out at early ages, in order to attempt to explain the psychoemotional profile of the cyberbullying victims, and thereby prevent potential bullying situations.…”
Section: Introductionmentioning
confidence: 99%
“…El trabajo planteado forma parte de una línea de investigación sobre bullying/cyberbullying que se inició en 2003, y se ha configurado con sucesivos trabajos (Garaigordobil, 2013;2017a;2017b); (Garaigordobil & Oñederra, 2008;2009;; (Garaigordobil & Martínez-Valderrey, 2018); (Machimbarrena & Garaigordobil, 2017). Este estudio tiene como principal objetivo llevar a cabo una revisión sistemática de las investigaciones que han explorado la prevalencia de bullying/ cyberbullying en los países Latinoamericanos.…”
Section: Introductionunclassified
“…Regarding school-related factors, having a good relationship with peers and teachers [14] reduces the risk of being involved in bullying. On the other hand, the perception of an inappropriate school climate [43], feeling a lack of safety at school [33,44], attending a public school [36,45] and large school size [21] increase the risk of being involved in bullying. Further, community factors, such as having problems with neighbors [28], concentrated poverty in the neighborhood and change of residence or residential instability [36] increase the risk of being involved in bullying, as a victim or a bully-victim.…”
Section: Introductionmentioning
confidence: 99%